2001
DOI: 10.1046/j.1440-6047.2001.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the significance of dietary folate from wild vegetables in Vietnam

Abstract: Data on the overall dietary folate intakes among high-risk groups in poor countries is very limited. Vegetables are considered good sources but the evaluation of their contribution is hampered by the lack of data on folate concentrations in many traditional foods. Data on the analysis of folate concentrations in 16 wild vegetables used in the Mekong Delta and the Central Highlands in Vietnam and an evaluation of the relative importance of different foods in folate intakes of women is presented. Vegetable sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…However, these contributions cannot be compared with the present results because they included nutrient-rich foods from wild animals in their wild foods. Ogle and co-workers using a simple 7 day food frequency questionnaire (FFQ), found that WEPs made important contributions to the β-carotene, Vitamin C, calcium and iron intakes in the Mekong Delta in Vietnam (Ogle et al 2001a), that wild vegetables contributed significantly to the overall micronutrient intake (calcium, iron, Vitamin A, thiamine, riboflavin, niacin, Vitamin C) (Ogle et al 2001b) and that wild vegetable consumption was responsible for 21 % and 14 % of the folate intake of women in the Mekong Delta and the Central Highlands, respectively (Ogle et al 2001c). Termote et al (2012) reported rare WEP consumption and small contributions to the dietary intake of rural women in a highly biodiverse region in DR Congo.…”
Section: Discussionmentioning
confidence: 99%
“…However, these contributions cannot be compared with the present results because they included nutrient-rich foods from wild animals in their wild foods. Ogle and co-workers using a simple 7 day food frequency questionnaire (FFQ), found that WEPs made important contributions to the β-carotene, Vitamin C, calcium and iron intakes in the Mekong Delta in Vietnam (Ogle et al 2001a), that wild vegetables contributed significantly to the overall micronutrient intake (calcium, iron, Vitamin A, thiamine, riboflavin, niacin, Vitamin C) (Ogle et al 2001b) and that wild vegetable consumption was responsible for 21 % and 14 % of the folate intake of women in the Mekong Delta and the Central Highlands, respectively (Ogle et al 2001c). Termote et al (2012) reported rare WEP consumption and small contributions to the dietary intake of rural women in a highly biodiverse region in DR Congo.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned by Tamura (1998), we must keep in mind that previously estimated dietary folate requirement may have been underestimated and folate bioavailability from our diet may have been overestimated. In many countries where folic-acid fortification of cerealgrain products is not mandatory, vegetables are the major contributors of folate (de Bree et al, 1997;Vahteristo et al, 1997;Iwatani et al, 2003;Ogle et al, 2001). Since vegetables are not always consumed in the raw state and cooking results in large folate losses, the information on folate content of raw vegetables alone does not make it possible to estimate dietary folate intake accurately.…”
Section: Discussionmentioning
confidence: 99%
“…The nutraceutical value and the antioxidant activity of wild, semi-cultivated or neglected vegetables is regarded worldwide as an important area of the nutritional and phytotherapic research (Lionis et al, 1998;Grivetti and Ogle, 2000;Karakaya et al, 2001;Ogle et al, 2001aOgle et al, , 2001bOgle et al, , 2001cJohnson and Grivetti, 2002;Owen and Johns, 2002;Coulaidis et al, 2003;Ogle et al, 2003;Zeghichi et al, 2003aZeghichi et al, , 2003bEl and Karakaya, 2004).…”
Section: Introductionmentioning
confidence: 99%